Challenges faced by teachers to use multimedia in classroom and students’ perception from it: a case study on a selected college in Bangladesh - Azad, Abul Kalam (Journal of Management and Business Education, 2024)
The increasing popularity of multimedia-based classes (MMCs) can be attributed to their efficacy and the favorable reception they have received from students. Bangladeshi educational institutions face challenges to incorporate multimedia-based classes (MMCs) due to several inside and outside barriers relative to teachers, but there is a little literary work on the challenges faced by teachers in Bangladeshi government college context as well as students’ perception on multimedia-based classes. Bangladeshi government college teachers like Cumilla Victoria Government College (CVGC) face a number of challenges to incorporate MMCs. Solutions are urgently needed to improve the teaching-learning environment of Bangladeshi Government Colleges. For this purpose 9 teachers and 9 students of CVGC were chosen by following qualitative research approach. Case study and FGD were done into both groups of respondents. Besides those, observation in classroom was done by the researcher. The study discloses that the teachers face a number of challenges to use multimedia in classroom. The major challenges have been found as inappropriate classrooms, lack of efficiency of teachers on multimedia content development, lack of proper steps from authorities and large number of students in classrooms. Both teachers and students acknowledge that utilizing multimedia in teaching-learning is the most effective approach to foster long-lasting connection within classroom settings. Additionally, it has been observed that MMCs have the potential to exhibit enhanced performance. The solutions to the challenges should be viewed from all levels like personal to administrative levels for ensuring the quality education of competitive world.